In the Conditions of Uzbekistan Principal Principles of Organization of Culture and Recreation Parks - Karimov Ulugbek Nurmamatovich; Musurmonova Munira Musurmonqizi (Researchparks Publishing, 2022)
The article scientifically and theoretically examines the basic principles of the design of